Heterozygous loss-of-function variants in DOCK4 cause neurodevelopmental delay and microcephaly - Charlotte Herbst; Viktoria Bothe; Meret Wegler; Susanne Axer-Schaefer; Séverine Audebert-Bellanger; Jozef Gecz; Benjamin Cogne; Hagit Baris Feldman; Anselm H. C. Horn; Anna C. E. Hurst; Melissa A. Kelly; Michael C. Kruer; et al. (Human Genetics, 2024)
Neurons form the basic anatomical and functional structure of the nervous system, and defects in neuronal differentiation or formation of neurites are associated with various psychiatric and neurodevelopmental disorders. Dynamic changes in the cytoskeleton are essential for this process, which is, inter alia, controlled by the dedicator of cytokinesis 4 ( DOCK4 ) through the activation of RAC1 . Here, we clinically describe 7 individuals (6 males and one female) with variants in DOCK4 and overlapping phenotype of mild to severe global developmental delay. Additional symptoms include coordination or gait abnormalities, microcephaly, nonspecific brain malformations, hypotonia and seizures. Four individuals carry missense variants (three of them detected de novo) and three individuals carry null variants (two of them maternally inherited). Molecular modeling of the heterozygous missense variants suggests that the majority of them affect the globular structure of DOCK4. In vitro functional expression studies in transfected Neuro-2A cells showed that all missense variants impaired neurite outgrowth. Furthermore, Dock4 knockout Neuro-2A cells also exhibited defects in promoting neurite outgrowth. Our results, including clinical, molecular and functional data, suggest that loss-of-function variants in DOCK4 probable cause a variable spectrum of a novel neurodevelopmental disorder with microcephaly.

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)